Improved LMI-based conditions for designing of PD-type ILC laws for linear batch processes over two-dimensional setting - Maniarski, Robert; Paszke, Wojciech (1975- ); Tao, Hongfeng; Hao, Shoulin
This paper considers the problem of designing of iterative learning control (ILC) lawsfor linear batch processes. Unlike the majority of existing results about ILC law designfor linear batch processes over repetitive/two-dimensional setting where Lyapunov theory isapplied, this study is focused on formulating the ILC law design procedures by transformingit into an equivalent problem of (structural) stability analysis for a linear Roesser model fortwo-dimensional (2D) systems.
Keywords: PD-type iterative learning control; linear matrix inequality; batch processes